15. EVALUATION OF ANTIBIOTIC USE AND FACTORS INFLUENCING TREATMENT OUTCOMES IN THE INTENSIVE CARE UNIT, CHILDREN’S HOSPITAL 2 FROM JUNE 2022 TO JUNE 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: To survey the use of antibiotics and factors associated with treatment outcomes in the Intensive Care Unit (ICU) of the Children’s Hospital 2.Subjects and Methods: A descriptive cross-sectional, retrospective study on 350 medical records of children hospitalized in ICU from June 2022 to June 2023.Results: The most used antibiotics were vancomycin (83.4%) and carbapenem (78%). Among 3,103 medical orders evaluated for antibiotic appropriatenes, 7.7% were inappropriate in terms of antibiotic selection, and 5.7% were inappropriate in terms of antibiotic dosage. The overall treatment success rate was 88.6%. Multivariate analysis revealed three factors associated with failure outcomes: septic shock (p = 0.002; OR 4.63; 95%CI 1.78 – 12.1), undergoing renal replacement therapy (p = 0.002; OR 6.53; 95%CI 1.99 – 21.49), and suspected invasive fungal infection (p = 0.002; OR 6.43; 95%CI 1.99 – 20.76) or confirmed invasive fungal infection (p = 0.001; OR 18.62; 95%CI 3.17 - 109.52).Conclusion: In general, antibiotic prescriptions and dosages were mostly adherent to current guidelines. Factors associated with failure treatment outcomes included septic shock, undergoing renal replacement therapy, and suspected or confirmed invasive fungal infections.
Keywords: antibiotic therapy, treatment effectiveness, ICU, pediatric